2018
DOI: 10.1016/j.mam.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids and leukocyte-endothelium adhesion: Novel anti-atherosclerotic actions

Abstract: Endothelial cells (ECs) play a role in the optimal function of blood vessels. When endothelial function becomes dysregulated, the risk of developing atherosclerosis increases. Specifically, upregulation of adhesion molecule expression on ECs promotes the movement of leukocytes, particularly monocytes, into the vessel wall. Here, monocytes differentiate into macrophages and may become foam cells, contributing to the initiation and progression of an atherosclerotic plaque. The ability of omega-3 (n-3) polyunsatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 83 publications
(115 reference statements)
2
58
0
1
Order By: Relevance
“…Increased expression of adhesion molecules by endothelial cells induces monocytes to roll along and adhere to the endothelial wall. Monocytes then migrate into the vessel wall and differentiate into macrophages, and potentially, foam cells, which triggers the formation of atherosclerotic plaque . Various methods of preventing the expression of cellular adhesion molecules have been proposed, such as RNAi targeting or modulation of specific signaling pathways, such as TLR‐NF‐κB .…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of adhesion molecules by endothelial cells induces monocytes to roll along and adhere to the endothelial wall. Monocytes then migrate into the vessel wall and differentiate into macrophages, and potentially, foam cells, which triggers the formation of atherosclerotic plaque . Various methods of preventing the expression of cellular adhesion molecules have been proposed, such as RNAi targeting or modulation of specific signaling pathways, such as TLR‐NF‐κB .…”
Section: Discussionmentioning
confidence: 99%
“…PUFAs including EPA, docosapentaenoic acid (DPA) and DHA, while LA can be converted to AA and beyond [7]. The conversion of ALA into LC n-3 PUFAs may be important for the physiological effects of ALA [7].…”
Section: Introductionmentioning
confidence: 99%
“…PUFAs including EPA, docosapentaenoic acid (DPA) and DHA, while LA can be converted to AA and beyond [7]. The conversion of ALA into LC n-3 PUFAs may be important for the physiological effects of ALA [7]. Although the conversion efficiency may be limited in humans [8], ALA may constitute an alternative and important source of LC n-3 PUFAs given the greater availability of sources rich in ALA such as walnuts, flaxseed, green leafy vegetables and plant oils including canola and soybean oils [9] compared to marine-derived LC n-3 PUFAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, numerous in vitro and in vivo investigations have shown that omega-3 PUFAs are able to modulate diverse key steps involved in atherosclerotic plaque formation (reviewed in [44]). Specifically, omega-3 PUFAs exert potent anti-inflammatory properties in polarized macrophages [45,46] and are able to inhibit the expression of adhesion molecules by ECs [39,47], thus decreasing leukocyte infiltration into the vascular wall [48]. In ApoE -/mice, omega-3 PUFA treatments significantly attenuated the development and destabilization of atherosclerotic plaques [49].…”
Section: N-3 Polyunsaturated Fattymentioning
confidence: 99%